Equilibrium, Kinetic and Thermodynamic Study of Aniline Adsorption over Prepared ZSM-5 Zeolite - Abbas, Ammar S.; Hussien, Sally A. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Aniline and its derivatives are common contaminants in various wastewaters and represent a serious worry for societies health and a challenge to ecologists due to their dangers effects on to the human health. ZSM-5 zeolite was prepared from locally available materials (kaolin and rice husk) for adsorption of aniline from synthetic wastewater. Characterization of the prepared zsm-5, kinetics and thermodynamic of the adsorption process were investigated. The characterization results of the prepared zsm-5 zeolite showed that the surface area was 270.1 m2/g and pore volume 0.21828 cm3/g. The silica to alumina ratio (Si/Al) was 166. 47 and the sodium content was 11 wt. %. The atomic force microscope (AFM) results showed that the average particle diameter of the prepared adsorbent was 70.71nm. Langmuir isotherm better illustrated the adsorption process with maximum uptakes 8.3125 mg/g. Whereas, kinetics results of the adsorption process showed it the pseudo-second order in different operating temperatures. The calculated values of ΔG showed that the adsorption process was spontaneous, while the ΔH results illustrated the process to be exothermic nature of this process with negative values of ΔS.